Chemical forms and stabilization of phosphorus in manures from large-scale livestock and poultry farms - Xie Guoxiong; Wu Chongshu; Kong Zhangliang; Jiang Mingbei (浙江大学学报. 农业与生命科学版)
Intensive confined livestock and poultry production systems generate large quantities of manure by-products, which have the potential for being recycled on agricultural land. Beneficial use through land application is based on their ability to alter favorably soil properties. However, protecting environmental quality is a major consideration when developing management practices are carried out to use effectively manure by-products as a nutrient resource and soil conditioner in agricultural production system. To date, most of the environmental problems associated with land application of manure by-products have centered on the contamination of groundwater and surface water with nitrogen and phosphorus. High concentration and high water solubility of phosphorus in animal manures have become a limiting factor for agricultural safety application of manures. Optimum use of these by-products requires the knowledge of their composition not only in relation to beneficial uses but also to environmental implications.To understand the chemical form of phosphorus in manures of large-scale livestock and poultry farms, and to seek the ways to stabilize phosphorus in manures, 92 manure samples were collected from representative largescale farms in Zhejiang Province. The chemical forms of phosphorus in the manures were identified by the modified Hedley's phosphorus fractionation. Six amendments, including alum, calcium carbonate, gypsum, fly ash and two soil materials, were used to test their effects on the stability of phosphorus in the manures. One pig manure sample was mixed separately with alum, calcium carbonate, gypsum, and the fly ash at the rates of 0%, 2%, 4% and 6%, and the two soil materials at the rates of 0%, 5% and 10%, and it was incubated at room temperature for 30 days. The incubated materials were analyzed for bio-available phosphorus (P) , water extractable P and chemical forms of P.The results showed that the manures collected from Zhejiang Province had the characteristics of high phosphorus, high inorganic phosphorus ratio and high availability. The total phosphorus content in the manures ranged from 18.70 to 54.30 g/kg with a mean of 30.50 g/kg. Extractable inorganic phosphorus in the manures accounted for the total phosphorus up to 70.08%, averagely. Mean proportions of water soluble P, NaHCO3-P and HCl-P in total P were 20.03%, 29.59% and 22.93%, respectively. Meanwhile, the proportions of NaOH-P and residual P were only 14.64% and 12.81%. The incubation experiments indicated that all kinds of amendments had significant effects to stabilize phosphorus in the manure, and the effects increased with the increasing amount of amendments. The stability effects decreased in the order of alum>fly ash>calcium carbonate>soil material>gypsum.In conclusion, the application of the manures from large-scale livestock and poultry farms has a great environmental risk. It is suggested that the application rate of the manure should be limited based on allowable P loadings, and the addition of amendments, such as alum, calcium carbonate, gypsum, fly ash and soil materials, can stabilize P in the manures.